A legal study of the Security Offences (Special Measures) Act 2012: detention / Shaharul Othman, Mohamad Alias Rasman and Nurul Fatin Hussin - Othman, Shaharul; Rasman, Mohamad Alias; Hussin, Nurul Fatin (2012)
The Internal Security Act 1960 has been repealed on the 16th September 2011. As a result on 22nd June 2012, the Security Offences (Special Measure) Act 2012 has been introduced and gazetted. Due to this change, there are several issues been raised by public. In our project paper we will focus on the legal study on the Security Offences (Special Measures) Act 2012 concerning detention. Basically, in our First Chapter we emphasize on the problem statement, the objective of our study, literature review, and the provisional plan of the research. This has been done in our proposal before, what we present here is the edited and extra information which is relevant to our study. In Chapter Two of our study, we discuss on the definition of detention. Furthermore, we will touch on the legal aspect of the introduction of the new Act as well as the repealed ISA 1960. Under Chapter Three we laid down the issues concerning the new Act. The issues are concerning the preamble of the new Act, the consistency between the new Act and the Federal Constitution, and the power of arrest and detention as stated under Section 4 of the Security Offences (Special Measures) Act 2012. In Chapter Four, we will make a comparative study on the detention between the new Act with the Patriot Act 2001 of United States of America as well as the Internal Security Act of Singapore. Under this chapter we will look at the differences on the detention which been practiced by these countries. Chapter Five would be the last chapter on conclusion and recommendations. Some recommendations would be reference from the constitutionalist on what should be amended in the new Act.